TRENDS IN HEUTAGOGY RESEARCH ON ISLAMIC EDUCATION (2010–2024):: A Bibliometric Study From Scopus - Yulistiawati, Devy; Komariah, Aan; Suryana, Asep; Aedi, Nur (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study examines trends in heutagogy research in Islamic education published between 2010 and 2024 through a bibliometric analysis of Scopus-indexed publications. The study aims to map the development, thematic focus, and scholarly contributions of heutagogy as a self-determined learning approach and to highlight its relevance for strengthening learner autonomy in Islamic educational contexts. Using a bibliometric review design, data were collected from the Scopus database through keyword-based searches related to heutagogy, self-determined learning, and Islamic education, with filters applied for publication year and document type. A total of 175 documents were analyzed using bibliometric mapping techniques, including publication trend analysis, geographical distribution, and co-word analysis, supported by VOSviewer software. The results indicate a consistent growth in publications with an annual increase of 10.79%, dominated by contributions from the United Kingdom, Australia, Indonesia, and Malaysia. Keyword analysis reveals core themes such as self-determined learning, andragogy, and online learning, demonstrating the close relationship between heutagogy and digital learning environments. Nevertheless, gaps remain in the application of heutagogical principles to Islamic education, particularly in teacher education, curriculum design for PAI, and technology-integrated learning models. The study concludes that heutagogy offers significant potential for advancing autonomous, reflective, and lifelong learning within Islamic education in the digital era.